2017
DOI: 10.1111/dar.12514
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from witnessing parental violence during childhood to involvement in intimate partner violence in adult life: The roles of depression and substance use

Abstract: Intergenerational transmission models of IPV through exposure during childhood can help to explain the high rates of domestic violence in Brazil. Our findings provide evidence to implement targeted prevention strategies where they are needed most: the victims of premature adverse experiences. [Madruga CS, Viana MC, Abdalla RR, Caetano R, Laranjeira R. Pathways from witnessing parental violence during childhood to involvement in intimate partner violence in adult life: The roles of depression and substance use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
2
26
0
9
Order By: Relevance
“…However, Madruga et al . found that although witnessing parental violence was independently associated with being a victim of IPV, IPV perpetration was not associated with witnessing parental violence when experience of direct violence as a child was controlled for. Madruga found that the association between witnessing parental violence and being a victim of IPV was mediated by depressive symptoms and by alcohol and cocaine use .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However, Madruga et al . found that although witnessing parental violence was independently associated with being a victim of IPV, IPV perpetration was not associated with witnessing parental violence when experience of direct violence as a child was controlled for. Madruga found that the association between witnessing parental violence and being a victim of IPV was mediated by depressive symptoms and by alcohol and cocaine use .…”
mentioning
confidence: 92%
“…There is also need to take into account adverse child events in interventions to address IPV perpetration, as two studies in this special issue highlight the association between IPV perpetration and trauma [20,21]. However, Madruga et al [22] found that although witnessing parental violence was independently associated with being a victim of IPV, IPV perpetration was not associated with witnessing parental violence when experience of direct violence as a child was controlled for. Madruga found that the association between witnessing parental violence and being a victim of IPV © 2017 Australasian Professional Society on Alcohol and other Drugs Drug and Alcohol Review (January 2017), 36, 3-6 DOI: 10.1111/dar.12526 bs_bs_banner was mediated by depressive symptoms and by alcohol and cocaine use [22].…”
mentioning
confidence: 98%
“…Ao procurar elaborar novos significados e romper com reducionismos, o princípio do recurso organizacional revela que ações e vivências violentas nos relacionamentos são produtos e produtores de outras experiências e condutas. Este aspecto torna-se claro na bidirecionalidade, evidenciada em diversos estudos nacionais e internacionais, em que ambos os sexos, mutuamente se agrediam e eram agredidos (FLAKE et al, 2013;BARREIRA;LIMA;AVANCI, 2013;BARREIRA et al, 2014;DARDIS et al, 2014;OLIVEIRA et al, 2014;TANAKA;WEKERLE, 2014;BESERRA et al, 2015;LINDNER, 2015;ALLY et al, 2016;CECCHETTO et al, 2016;FILIPA, 2016;MADRUGA et al, 2017;COELHO; SILVA; LINDNER, 2018).…”
Section: Princípio Do Recurso Organizacionalunclassified
“…v) Adolescentes do sexo feminino e masculino perpetrando e sofrendo violência patrimonial, destruindo objetos ou qualquer forma de bens do outro, podendo ter valor sentimental ou não, na mesma proporção (OLIVEIRA et al, 2014;FILIPA, 2016;MADRUGA et al, 2017).…”
Section: Princípio Do Recurso Organizacionalunclassified
See 1 more Smart Citation